Electro collisions with molecular nitrogen in its ground and electronically excited states using the R-matrix method. (7th June 2021) - Su, He; Cheng, Xinlu; Zhang, Hong; Tennyson, Jonathan
Abstract: A comprehensive study of electron collisions with the X 1 Σg + ground state as well as the metastable A 3 Σu + and a 1 Πg excited states of the N2 molecule is reported using the fixed-nucleus R-matrix method. Integral elastic scattering and electronic excitation cross sections from the X 1 Σg + ground state to the eight lowest electronic states, A 3 Σu +, B 3 Πg, W 3 Δu, B′ 3 Σu −, a 1 Πg, a′ 1 Σu −, w 1 Δu and C 3 Πu, overall agree well with the available experimental and theoretical results although updates of some recommended values are suggested. Accurate electron impact electronic transition cross sections starting from the A 3 Σu + and a 1 Πg metastable excited states are reported. The total summed electronic transition cross sections from the a 1 Πg state is dominant: an order of magnitude higher than those of the X 1 Σg + ground state. The de-excitation cross sections generally show a downward trend with increasing incident electron energy, which is different from the elastic and electronic excitation cross sections which generally increase with collision energy. There is a prominent 2 Πu symmetry resonance peak at 2.8 eV for electronic de-excitation scattering of a 1 Πg → B 3 Πg, which significantly contributes to the total summed cross sections from the a 1 Πg excited state. The present results provide a new insight which will aid understanding of electron spectra in the atmosphere of the Earth and Titan.